Comparative Quality Investigation of Rolled and Flat Carbon Steel Plates in Drilling - Sivarao, Subramonian; Taufik, , (2009)
Comparative investigation of machining quality of rolled steel plate and flat plate are studied, where, the effects of cutting speed, feed rate and numbers of holes drilled are taken into account. For this purpose, AISI 1045 carbon steel was drilled in dry machining conditions using CNC HAAS milling machine. Drilling process was carried out with 10mm diameter twist drill tool with 118° point angle. Ranges of the feed rate and cutting speed recommended by the tool manufacturer were tested to investigate the surface quality drilled holes. The Surf-Test SJ-301 has been used to measure the micro defects on drilled holes. In the experiments, surface roughness found to be increased in pattern with the holes drilled. The results also discusses about the influences of cutting speed and feed in determining the surface finish of holes produced.